IDENTIFIKASI POTENSI DAN STRATEGI PENGEMBANGAN BUDIDAYA IKAN BANDENG (Chanos chanos Forskall) DI DESA PANAIKANG KECAMATAN SINJAI TIMUR KABUPATEN SINJAI - Megawati Jamal; Andi Muhibuddin; Erni Indrawati (Journal of Aquaculture and Environment, 2018)
Efforts to anticipate the challenges and threats posed from aquaculture activities, it is necessary the application of the basic principles of responsible aquaculture. For example by applying environmental approach in the development of aquaculture. The purpose of this study is overview of the application of the principles of Ecosystem Approach to Aquaculture (EAA) in cultivation and analyze the development strategy of cultivating fish. Implemented in January to March 2016. Technical analysis is conducted using the method of assessment indicators composite index in the EAA. Simple approach to engineering composites Flag Modeling multi-criteria analysis. Research shows that the institutional dimension of good in implementing the EAA, the economic dimension enough in implementing the EAA, and the dimensions of ecology, sustainability, and social activities less apply EAA.